Translation Strategies of Idiomatic Expressions in Marketing 4.0: Moving from Traditional to Digital Written by Philip Kotler - Diana Az Zahra Mahesti; Lina Meilinda (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2022)
The research analyzes the translation strategies of idiomatic expressions found in a marketing monograph entitled Marketing 4.0: Moving from Traditional to Digital and Marketing 4.0: Bergerak Dari Tradisional ke Digital. This study aims to identify the use of translation strategies and the most used strategy to translate idiomatic expressions in those monographs. The theory applied in this study is from Mona Baker (2018). The results of this study revealed that the translation strategies found are using an idiom of similar meaning and form (SMF), using an idiom of similar meaning but dissimilar form (SMDF), translation by paraphrase, and translation by the omission of a play on idiom. Moreover, the most frequently used strategy found is the paraphrasing strategy (69.23%). The results of this study are expected to provide a better understanding of translation strategies for idiomatic expressions to the readers.